The Influence of Educational Videos About Factors Influencing Stunting Through Twitter Social Media on the Knowledge of Teenagers at SMA Negeri 4 Samarinda - Adinda Siti Rohmah Mawaddah; Rini Ernawati; Enok Sureskiarti (PROMOTOR, 2024)
High levels of stunting have a negative impact on children's development and learning abilities, increasing their risk of infection, and making them more vulnerable to disease. To prevent stunting in future generations, it is necessary to intervene early, especially in the adolescent age group. Teenagers play an important role and have great potential in preventing and breaking the cycle of stunting. This research aims to increase teenagers' knowledge about the factors that influence stunting through the social media platform Twitter. Adolescent health promotion can be effectively carried out through social media. This research method is quantitative, using a Pretest-Posttest design with a Control Group. Comparisons were made between the experimental group who were given stunting education via videos on Twitter and the control group who did not receive the intervention. The number of samples for this research was 40 students in class XI. The research instrument is a questionnaire, and statistical analysis uses the Paired Sample t-test. The research results showed that the average knowledge value in the experimental group before education was 8.85, and after education it was 12.75, while in the control group without intervention, the initial average value of 7.25 changed to 7.05. With a P-value = 0.000 (p <α 0.05), H0 is rejected, indicating that there is a significant influence of educational videos about factors influencing stunting via Twitter social media on adolescent knowledge at SMA Negeri 4 Samarinda.